Non-canonical Interaction Between O-Linked N-Acetylglucosamine Transferase and miR-146a-5p Aggravates High Glucose-Induced Endothelial Inflammation - Lo, Wan-Yu; Wang, Shou-Jie; Wang, Huang-Joe (Frontiers in Physiology, 2020)
Background and Aims: Increased O-GlcNAc transferase (OGT)–induced O-linked N-acetylglucosamine (O-GlcNAc) post-translational modification is linked with diabetic complications. MicroRNA-146a-5p (miR-146a-5p) is a negative inflammatory regulator and is downregulated in diabetes. Here, we investigated the interaction between miR-146a-5p and OGT. Methods: Human aortic endothelial cells (HAECs) were stimulated with high glucose (25 mM) and glucosamine (25 mM) for 24 h. Western blot, real time PCR, bioinformatics analysis, luciferase reporter assay, miR-146a-5p mimic/inhibitor transfection, siRNA OGT transfection, miR-200a/200b mimic transfection, and OGT pharmacological inhibition (ST045849) were performed. The aorta from miR-146a-5p mimic-treated db/db mice were examined by immunohistochemistry staining. Results: HG and glucosamine upregulated OGT mRNA and protein expression, protein O-GlcNAcylation, and IL-6 mRNA and protein expression. Real time PCR analysis found that miR-146a-5p was decreased in HG- and glucosamine-stimulated HAECs. This suggested that OGT-induced protein O-GlcNAcylation as a mechanism to downregulate miR-146a-5p. Bioinformatic miR target analysis excluded miR-146a-5p as a post-transcriptional regulator of OGT. However, a luciferase reporter assay confirmed that miR-146a-5p mimic bound to 3´-UTR of human OGT mRNA, indicating that OGT is a non-canonical target of miR-146a-5p. Transfection with miR-146a-5p mimic and inhibitor confirmed that miR-146a-5p regulated OGT/protein O-GlcNAcylation/IL-6 expression levels. Furthermore, OGT siRNA transfection, miR-200a/miR-200b mimic transfection, and ST045849 increased HG-induced miR-146a-5p expression levels, indicating that HG-induced miR-146a-5p downregulation is partially mediated through OGT-mediated protein O-GlcNAcylation. In vivo, intravenous injections of miR-146a mimic decreased endothelial OGT and IL6 expression in db/db mice. Conclusion: A non-canonical positive feedback interaction between miR-146a-5p and OGT is involved in a vicious cycle to aggravate HG-induced vascular complications.